Shwedish experience of management of secondary resources cadastre - Peresoliak, V. (Land Management, Cadastre and Land Monitoring, 2019)
The article analyzes the problems of functioning and dynamics of the management reform and management of secondary resource cadastre in the Kingdom of Sweden. The scientific paradigms of the analysis of the use of secondary resources of the Kingdom of Sweden are presented.          Secondary or they can also be called technogenic resources annually "reproduced" at a significant and rapid pace and increasingly occupy new territories of natural landscapes. The growth rates of waste in the industrialized countries of the world exceed twice the dynamics of material production and natural population growth. In each civilized country, the accumulation of solid industrial and domestic wastes causes the risks of environmental disasters that need to be utilized for their solution. Ukraine is no exception.          Establishing and maintaining a cadastre of secondary resources at the state level provides an opportunity to make managerial decisions on preventing environmental disasters and bringing technogenic landscapes to the fore.          For example, the Kingdom of Sweden considered how the philosophy of society, dealing with secondary resources and managing their cadastre changes with the adoption of targeted state management decisions..Keywords: cadastre, waste, secondary resources, recycling.